2z+6+3z=-34

Simple and best practice solution for 2z+6+3z=-34 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2z+6+3z=-34 equation:


Simplifying
2z + 6 + 3z = -34

Reorder the terms:
6 + 2z + 3z = -34

Combine like terms: 2z + 3z = 5z
6 + 5z = -34

Solving
6 + 5z = -34

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 5z = -34 + -6

Combine like terms: 6 + -6 = 0
0 + 5z = -34 + -6
5z = -34 + -6

Combine like terms: -34 + -6 = -40
5z = -40

Divide each side by '5'.
z = -8

Simplifying
z = -8

See similar equations:

| 5(x+1)=40 | | 5g=2h-6 | | 2(4x-3)-8-2x=4 | | -9+12+4(3x-3)=7(x-2)-4x+14 | | 2(x-4)-3x=-4(x+2)+3x | | x^4+10x^2-299=0 | | 4y-8-2y=2-(-2) | | -(8(0)+4)=4(0)-2(6(0)+2) | | 4x^2-20xy-7x+35y= | | 3x^2+23x-8= | | 3(x+2)-2=6(x+1)-3x | | 4y-8-27=2-(-2) | | 14x-79=8x-25 | | 4x-(x+3)=6 | | -10+5y-35=-4 | | -10+5-35=-4 | | 7a-b=15 | | 175=85+(15+8)w | | (x-78)+x=180 | | 3b-12=6b-8 | | m+1=-1+3m | | -4y+36=4(3y-3) | | 5x-1x=15 | | 3.4x+5=22 | | 2.5x+2.5=12.5 | | 2.1(a+0.5)=-2.1(a+20) | | -5t-7t=2t | | -5x-24=2x+11 | | 5(c-1)-2(c+3)-2c=-8 | | 23=-3m+2 | | 11-4z=-27 | | 4y-14=6y-16 |

Equations solver categories